Financial Strengthening Strategies in Increasing Company Competitiveness Multinational - Rahman, Fatmawati A; Masmarulan, Masmarulan; Rostini, Rostini; Muhammad, A Fadel; Bakri, Risna Melati Sukma (PT. Riset Press International, 2024)
In the era of globalization, multinational companies face complex challenges and opportunities in various jurisdictions. Financial strengthening is a key strategy to increase a company's competitiveness in a dynamic global market. This research examines how efficient financial management, managing foreign exchange risks, optimizing capital structure, and investing in technology can support the stability and growth of multinational companies. Through in-depth literature analysis, this research highlights the importance of integrated and holistic financial strategies to ensure liquidity, reduce risks and maximize profits. With a sustainable and responsible approach, multinational companies can achieve competitive advantage and contribute to inclusive global economic development.